Outbreak investigation, molecular detection, and characterization of foot and mouth disease virus in the Southern part of Bangladesh - Ali, Md Zulfekar; Islam, Eusha; Giasuddin, Md (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The objective of the study was to investigate Foot and Mouth Disease virus (FMDV) outbreak in cattle in the Sarankhola Upazila under Bagerhat district of Bangladesh with isolation, identification, and molecular characterization of FMDV during April 2018. Materials and Methods: This Upazila is located at southern border of Bangladesh and surrounded by mangrove forest Sundarban. The outbreak investigation team collected epidemiological data from outbreak location. In addition, the team collected a total of 30 (15 calves, 15 adult) tongue epithelial tissue samples from a clinically FMD-affected cattle. The confirmation of FMDV and its three serotypes (A, O, and Asia-1) was performed by Reverse Transcriptase Polymerase Chain Reaction (RT-PCR). An amplified product of the VP1 region of FMDV genome was sequenced by Sanger sequencing method after cultivation and reconfirmation of FMDV into the BHK21 cell line. Genetic variability was studied by constructing a phylogenetic tree. Results: The investigation survey was carried out in overall 8,393 (8,393/15,580; 53.89%) cases including 3,050 (3,050/8,393; 36.34%) cases in calf and 5,343 (5,343/8,393; 59.77%) cases in adult cattle. The overall case fatality rate (CFR) was recorded as 2.27% (354/15,580) with significantly highest CFR in the calf (71.46%; 253/354) compared to an adult. The collected all 30 samples found with FMDV positive and mixed infection of all samples with serotype Asia-1 and serotype O were observed. In BHK 21 cell line, the eight FMDV positive samples showed a typical cytopathic effect during the third passage. Finally, DNA sequence data of two isolates found closely related with the isolates of bordering country India and Myanmar. Conclusion: The investigation identified the risk factors involved in an outbreak of FMDV, namely, sharing the common paddy land after harvesting, no FMD vaccination, the interaction between cattle and wildlife, and cross bordering movement. J. Adv. Vet. Anim. Res., 6(3): 346-354, September 2019